Exploratory making: site inspired making as a tool for site analysis and design - Moore, Wesley (Kansas State University, 2016)
Design tools (the method of making a designer uses to conceptualize or communicate the assembly of an object) are not simply secondary instruments to communicate designs through, but are the primary media through which designers contemplate and process design problems. Designers should utilize tools, whether digital or analog, with an awareness of each tool’s limitations and advantages and the possibilities they provide to each step of the design process. The intent of this report is to study how site inspired making methods can be used to observe and reveal information about a site, and thus contribute to the site analysis phase of design. Site inspired making methods are developed in this report through an exploratory research process. Exploratory research is a qualitative method used to provide flexibility in developing knowledge about a topic. An exploratory process was chosen to allow my focuses to shift as I make and reflect so my findings arise as I conduct the studies, not just from an initial hypothesis. Through an exploratory research process of making and reflecting this report answers the question: How do various methods of making develop and document my understanding of the site? Exploratory methods of drawing and sculpting are used to observe and reveal site information, and develop site-inspired artistic works. The site is a small, wooded lot and cove of Tuttle Creek Lake located northwest of Manhattan, Kansas. The research process is divided into an investigation phase in which I explored initial drawing and sculpting methods and an application phase in which I created a sculpture and series of drawings inspired by the site. I documented site conditions through observational drawing; revealed patterns and textures by drawing with and on site materials; developed parametric studies of balancing sculptures; discovered crystallization patterns by splattering ink on a frozen lake; designed a balancing sculpture inspired by the motion of ice sheets and driftwood on water; and created frost drawings by applying ink to soaked and frozen watercolor paper. Each method revealed different site qualities and informed my understanding of the site.
Keywords: Site analysis; Experiential; Making; Mobile; Ice; Exploratory